Multiple Vibrio vulnificus strains in oysters as demonstrated by clamped homogeneous electric field gel electrophoresis. - Buchrieser, C (1995)
Clamped homogeneous electric field gel electrophoresis and a computer program for managing electrophoresis banding patterns (ELBAMAP) were used to analyze genomic DNA of 118 Vibrio vulnificus strains, isolated from three oysters by direct plating. Analysis with SfiI resulted in 60 restriction endonuclease digestion profiles (REDP), while analysis with SrfI produced 53 different REDP. Similarities between REDP ranged from 7 to 93%. Principal-component analysis showed that the strains were heterogeneous.